Pengaruh pemberian benalu teh dan benalu mangga terhadap kadar malondialdehid serum pada tikus wistar jantan - Ma'ruf, Muhammad; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid; Kumalasari, Eka (University Of Darussalam Gontor, 2025)
Tea mistletoe and mango mistletoe are plants known to possess strong antioxidant activity. The antioxidants in these plants play a role in combating free radicals, inhibiting cell oxidation, and reducing the risk of cellular damage. The active compounds present in tea and mango mistletoe have the potential to reduce malondialdehyde (MDA) levels caused by free radical exposure. This study aimed to evaluate the effect of tea and mango mistletoe (BTBM) administration on MDA levels in male Wistar rats induced with deoxycorticosterone acetate (DOCA)-salt. This study used 25 male Wistar rats, divided into five groups: normal, control (DOCA-salt), and three treatment groups receiving BTBM at doses of 50, 100, and 200 mg/kgBW. The study lasted 28 days, beginning with BTBM administration for 14 days, followed by DOCA-salt induction alongside BTBM administration from day 15 to day 28. MDA levels were measured using the Thiobarbituric Acid Reactive Substances (TBARS) method with a UV-Vis spectrophotometer at a wavelength of 531 nm. Data were statistically analyzed using one-way ANOVA, followed by a Post Hoc Tukey test to determine differences between groups. The results showed that BTBM administration at a dose of 50 mg/kgBW significantly (p<0.05) reduced MDA levels compared to the control group. Thus, it can be concluded that the combination of tea and mango mistletoe has potential as an antioxidant agent in reducing MDA levels, with 50 mg/kgBW as the optimal dose in the DOCA-salt-induced rat model.